Pengaruh Lingkungan Kerja, Komitmen Organisasi, dan Budaya Organisasi terhadap Kepuasan Kerja Tenaga Kependidikan Universitas Graha Nusantara Padangsidimpuan - Rizky Mery Octavianna Lubis; Yusuf Pathuansyah; Mahrani Mahrani (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the influence of work environment, organizational commitment, and organizational culture on the job satisfaction of educational staff at Universitas Graha Nusantara Padangsidimpuan. The research employed a quantitative approach with an explanatory survey design. The population consisted of 52 educational staff members, and a total sampling technique was applied, resulting in 52 respondents. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression analysis. The findings indicate that the work environment, organizational commitment, and organizational culture have a positive and significant effect on job satisfaction, both partially and simultaneously. The coefficient of determination (R²) of 0.779 demonstrates that 77.9% of the variance in job satisfaction is explained by the three independent variables. Among the variables, the work environment was found to be the most dominant factor influencing job satisfaction. These findings highlight the importance of strengthening organizational factors to enhance the job satisfaction of educational staff.